Buffering growth variations against water deficits through timely carbon usage - Pantin, Florent; Fanciullino, Anne-Laure; Massonnet, Catherine; Dauzat, Myriam; Simonneau, Thierry; Muller, Bertrand (Frontiers in Plant Science, 2013)
Water stresses reduce plant growth but there is no consensus on whether carbon metabolism has any role in this reduction. Sugar starvation resulting from stomatal closure is often proposed as a cause of growth impairment under long-term or severe water deficits. However, growth decreases faster than photosynthesis in response to drought, leading to increased carbohydrate stores under short-term or moderate water deficits. Here, we addressed the question of the role of carbon availability on growth under moderate water deficits using two different systems. Firstly, we monitored the day/night pattern of leaf growth in Arabidopsis plants. We show that a moderate soil water deficit promotes leaf growth at night in mutants severely disrupted in their nighttime carbohydrate availability. This suggests that soil water deficit promotes carbon satiation. Secondly, we monitored the sub-hourly growth fluctuations of clementine fruits in response to daily, natural fluctuation in air water deficit, and at contrasting source-sink balance obtained by defoliation. We show that high carbohydrate levels obtained under favourable source-sink balance prevent excessive, hydraulic shrinkage of the fruit during days with high evaporative demand, most probably by modulating osmotic adjustment. Together, our results contribute to the view that growing organs under moderate soil or air water deficit are not carbon starved, but use soluble carbohydrate in excess to partly release a hydromechanical limitation of growth.